Evolving microstructure, magnetic properties and phase transition in a mechanically alloyed Ni0.5Zn0.5Fe2O4 single sample - Ismail, Ismayadi; Hashim, Mansor; Kanagesan, Samikannu; Ibrahim, Idza Riati; Nazlan, Rodziah; Wan Ab Rahman, Wan Norailiana; Abdullah, Nor Hapishah; Mohd Idris, Fadzidah; Bahmanrokh, Ghazaleh; Shafie, Mohd Shamsul Ezzad; Manap, Masni (Elsevier, 2014)
We report on an investigation to unravel the dependence of magnetic properties on microstructure while they evolve in parallel under the influence of sintering temperature of a single sample of Ni0.5Zn0.5Fe2O4 synthesized via mechanical alloying. A single sample, instead of the normally practiced approach of using multiple samples, was sintered at various sintering temperatures from 500 °C to 1400 °C. The morphology of the samples was studied by means of scanning electron microscopy (SEM) equipped with EDX; density measurement was conducted using the Archimedes principle; and hysteresis measurement was carried out using a B–H hysteresisgraph system. XRD data showed that the first appearance of a single phase was at 800 °C and an amorphous phase was traced at lower sintering temperatures. We correlated the microstructure and the magnetic properties and showed that the important grain-size threshold for the appearance of significant ordered magnetism (mainly ferromagnetism) was about ≥0.3 µm. We found that there were three stages of magnetic phase evolution produced via the sintering process with increasing temperatures. The first stage was dominated by paramagnetic states with some superparamagnetic behavior; the second stage was influenced by moderately ferromagnetic states and some paramagnetic states; and the third stage consisted of strongly ferromagnetic states with negligible paramagnetic states. We found that three factors sensitively influenced the sample's content of ordered magnetism—the ferrite-phase crystallinity degree, the number of grains above the critical grain size and the number of large enough grains for domain wall accommodation.